2005
DOI: 10.1590/s0100-40422005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de biocatálise enantiosseletiva de lipases microbianas

Abstract: Recebido em 18/5/04; aceito em 12/11/04; publicado na web em 13/4/05 POTENTIAL OF ENANTIOSELECTIVE BIOCATALYSIS BY MICROBIAL LIPASES. Microbial lipases have a great potential for commercial applications due to their stability, selectivity and broad substrate specificity because many non-natural acids, alcohols or amines can be used as the substrate. Three microbial lipases isolated from Brazilian soil samples (Aspergillus niger; Geotrichum candidum; Penicillium solitum) were compared in terms of their stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
30

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 50 publications
0
31
1
30
Order By: Relevance
“…Incubation time (72 hours) was the same for both species. Burkert et al (2004), with Geotrichum sp., obtained enzymatic activity of 17 U/ml, after 50 hours of incubation, meanwhile Carvalho et al (2005), observed 12.8 U/ml, with Geotrichum candidum, after 72 hours. Both studies used olive oil as carbon source and quantified the fatty acids by titration.…”
Section: Mukundamentioning
confidence: 90%
“…Incubation time (72 hours) was the same for both species. Burkert et al (2004), with Geotrichum sp., obtained enzymatic activity of 17 U/ml, after 50 hours of incubation, meanwhile Carvalho et al (2005), observed 12.8 U/ml, with Geotrichum candidum, after 72 hours. Both studies used olive oil as carbon source and quantified the fatty acids by titration.…”
Section: Mukundamentioning
confidence: 90%
“…A diversidade de microrganismos existentes justifica a busca por novos produtores de enzimas (CARVALHO et al, 2005;LIMA et al, 2001). A identificação de novas fontes microbianas, principalmente não tóxicas ao organismo humano, é de interesse estratégico, pois, além de garantir o suprimento de enzimas aos mais variados processos industriais, tornam possível o desenvolvimento de novos sistemas enzimáticos que não podem ser realizados a partir de enzimas vegetais ou animais (OLIVEIRA et al, 2006).…”
Section: Seleção De Fungos Produtores De Lipasesunclassified
“…O fungo E 20 foi classificado como do gênero Penicillium, enquanto que os fungos E 9 e E 21 foram pertencentes ao gênero Aspergillus, sendo ambos reportados como bons produtores de lipases por Carvalho et al (2005) Maia et al (2001).…”
Section: Determinação Da Atividade Lipolíticaunclassified
“…16,17 In fact, lipases have been widely recognized as the most important group of biocatalysts for biotechnological applications. [18][19][20] They have been used to catalyze hydrolysis, esterification, transesterification and interesterification reactions, with extreme process simplicity, higher quality of the final product and excellent yield.…”
Section: Introductionmentioning
confidence: 99%
“…23 The immense biological diversity in the Amazon region and the importance of fungi as enzyme sources, has led to the search for new biocatalysts with special characteristics and possibilities for application in biotechnological processes. 16,28 The access to a wide range of lipase types has made them even more desirable for two additional reasons: (i) from the large number of lipases cited in the literature, only the enzymes of a few species have been shown to be stable and have biosynthetic capacities suitable for routine use in organic reactions; and (ii) many important problems remain unsolved in the application of lipases in certain industrial processes. 29 Considering the need for production processes which are more committed to the ideal of sustainability, this study aims to contribute to the broadening of knowledge regarding the biotechnological potential of fungi from the Amazon region, particularly those isolated from flora, as potential mycelium bound-lipase sources for application in the field of biocatalysis.…”
Section: Introductionmentioning
confidence: 99%